IMPROVING HEALTH CARE DELIVERY BY COMMUNITY HEALTH WORKERS THROUGH MOBILE PHONES - Nandasaba, Khisa Kevin (Machakos University, 2019)
Community health workers (CHWs) play a critical role in delivery of basic health care especially in rural communities where access to health care is a challenge. Most of these “first line” health care workers are ill equipped and do not have much support in their role. Majority of Community health workers are low skilled and operate far from formal health care system. Mobile phones have provided a unique opportunity for Community health workers. This technology has allowed access of health information through the internet to facilitate their work. They are able to acquire updated information on how to deal with certain ailments, protocols to be followed and even consult with medical practitioners. It has improved the attendance to clinics immensely through reminders sent to patients in the form of text messages. Adherence to medication has also been enhanced through the same approach. It has made the collection and transmission of information to relevant authorities easier, faster and efficient. This paper presents the application of mobile phone technology specifically among community health workers. A review of literature available on chwcentral.org, a platform devoted to research linked to community health work, forms the core of this paper. It delves into the opportunity that this technology provides for improvement of health care delivery to communities. It provides evidence that indeed mobile phones can contribute immensely to improving health care delivery through community health workers to communities in dire need of these services
Keywords: Community Health Workers; Health care delivery; Mobile phones; Improving